Steel cord and method for producing the same

CN122879998APending Publication Date: 2026-10-09INST OF RES OF IRON & STEEL JIANGSU PROVINCE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611387660.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

这些残余元素在冶炼过程中难以去除,在应用于帘线钢的生产中时,会导致拉拔断丝率高的问题

Benefits of technology

本申请基于高碳钢盘条的化学成分,提出残余元素因子σ,并根据残余元素因子σ控制生产工序及参数;热处理工序中,根据残余元素因子σ控制加热温度、保温时间、铅浴温度及铅浴时间,目的在于补偿残余元素如Cu、Ni、Cr等对过冷奥氏体稳定性和珠光体转变动力学的差异影响;σ值越高,残余元素偏聚越严重,奥氏体稳定性越强,因此需提高加热温度和铅浴温度,并延长保温时间与铅浴时间,以促进合金元素充分固溶和均匀扩散,确保铅浴等温转变后获得细密、均匀的索氏体组织,避免异常组织如马氏体、贝氏体和网状渗碳体析出,从而保证钢丝兼具高强度与良好塑性,提高后续拉拔及合股捻制性能的稳定性;镀黄铜工序中,随着残余元素因子σ增大,通过提高热扩散时的温度可以加快铜、锌原子在界面处相互扩散,进而形成组分稳定、均匀的黄铜镀层,抵消残余元素在钢丝基体界面富集阻碍扩散的不利影响,使得镀层中的铜含量维持在目标区间,同时配合热扩散时间的控制,可以避免温度过高引发的钢丝基体强度下降、表层脱碳,提升镀层与基体结合力,改善钢帘线与橡胶的粘合性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a steel cord and a production method thereof. In the production method, the steel cord is prepared from a high-carbon steel wire rod through the processes of mechanical peeling, rough drawing, intermediate drawing, heat treatment, copper plating, wet drawing and ply twisting in sequence; in the high-carbon steel wire rod, a residual element factor σ satisfies σ<=1.1%, σ=Cu+Ni+3(Cr+Mo+Sn)+15N+0.5(Sb+As); in the heat treatment process, the steel wire obtained in the intermediate drawing process is heated and then kept warm, and then lead bath is carried out, and according to the range of the residual element factor σ, the heating temperature, the keeping warm time, the lead bath temperature and the lead bath time are controlled; in the copper plating process, the steel wire after the heat treatment process is sequentially subjected to copper plating, zinc plating and thermal diffusion to obtain the steel wire with a copper plating layer, the thermal diffusion time is 10-25s, and according to the range of the residual element factor σ, the temperature during the thermal diffusion is controlled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of steel production and manufacturing technology, specifically relating to a method for producing steel cord, and also to a steel cord prepared based on the production method. Background Technology

[0002] Steel cord is a common rubber reinforcing material, widely used in radial tires of various automobiles, trucks, and aircraft. The production process of steel cord involves drawing high-carbon steel wire rods with a diameter of 5.5~6.5mm into fine filaments with a diameter of 0.175~0.35mm. To reduce the wire breakage rate during drawing, high requirements are placed on the metallurgical quality of the high-carbon steel wire rods, especially regarding the content of impurity elements, cleanliness, and drawing performance.

[0003] Electric arc furnace (EAF) smelting is widely used in the production of high-carbon steel wire rod due to its low carbon emissions. However, EAF smelting uses scrap steel as its main raw material, and during the production process, residual elements such as Cu, Ni, Cr, Sn, Sb, and As from the scrap steel inevitably enter the wire rod. These residual elements are difficult to remove during smelting, leading to a high wire breakage rate during drawing when used in the production of tire cord. Summary of the Invention

[0004] The purpose of this application is to provide a method for producing steel cord, and the steel cord produced by the method.

[0005] To achieve the above objectives, one embodiment provides a method for producing steel cord, wherein the steel cord is prepared from high carbon steel wire rod through a series of processes including mechanical peeling, rough drawing, intermediate drawing, heat treatment, brass plating, wet drawing, and strand twisting. The chemical composition of the high-carbon steel wire rod, by mass percentage, includes: C 0.68~0.86%, Si 0.10~0.30%, Mn 0.30~0.60%, S≤0.015%, P≤0.020%, Al≤0.005%, O≤0.003%, N≤0.005%, Cu≤0.35%, Ni≤0.30%, Cr≤0.30%, Mo≤0.015%, Sn≤0.015%, Sb≤0.015%, As≤0.015%, with the remainder being Fe and unavoidable impurities; wherein, the residual element factor σ≤1.1%, σ=Cu+Ni+3(Cr+Mo+Sn)+15N+0.5(Sb+As); In the heat treatment process, the steel wire obtained from the intermediate drawing process is heated and held at a certain temperature, followed by a lead bath. Specifically, when σ ≤ 0.3%, the heating temperature is (895 + 3000σ)℃ ~ (905 + 3000σ)℃, the holding time is (32 + 2000σ)s ~ (38 + 2000σ)s, the lead bath temperature is (525 + 3000σ)℃ ~ (535 + 3000σ)℃, and the lead bath time is (62 + 2000σ)s ~ (68 + 2000σ)s; when 0.3% < σ ≤ 0.7%, the heating temperature is (905 + 1500σ)℃ ~ (915 + 1500σ)℃, and the holding time is (… 38+1000σ)s~(43+1000σ)s, lead bath temperature is (535+1500σ)℃~(545+1500σ)℃, lead bath time is (68+1500σ)s~(73+1500σ)s; when 0.7%<σ≤1.1%, heating temperature is (915+1000σ)℃~(925+1000σ)℃, holding time is (43+500σ)s~(48+500σ)s, lead bath temperature is (545+1000σ)℃~(555+1000σ)℃, lead bath time is (73+1000σ)s~(78+1000σ)s; In the brass plating process, the steel wire that has undergone the heat treatment process is sequentially copper-plated, zinc-plated, and thermally diffused to obtain a steel wire with a brass coating. The thermal diffusion time is 10~25s. Specifically, when σ≤0.3%, the temperature during thermal diffusion is 540~550℃; when 0.3%<σ≤0.7%, the temperature during thermal diffusion is 550~560℃; and when 0.7%<σ≤1.1%, the temperature during thermal diffusion is 560~570℃.

[0006] As a further improvement to one embodiment, in the rough drawing process, when σ≤0.3%, the number of drawing passes is 6~7, the deformation amount of a single drawing pass is ≤21%, and the wire drawing speed is 7.0~8.0m / s; When 0.3% < σ ≤ 0.7%, the number of drawing passes is 8 to 9, the deformation per single drawing pass is ≤ 19%, and the drawing speed is 5.5 to 6.5 m / s; When 0.7% < σ ≤ 1.1%, the number of drawing passes is 10 to 11, the deformation per single drawing pass is ≤ 17%, and the wire drawing speed is 4.5 to 5.0 m / s.

[0007] As a further improvement to one embodiment, in the intermediate drawing process, when σ≤0.3%, the number of drawing passes is 7~8, the deformation of a single drawing pass is ≤20%, and the wire drawing speed is 12.0~13.0m / s; When 0.3% < σ ≤ 0.7%, the number of drawing passes is 9 to 10, the deformation per single drawing pass is ≤ 18%, and the wire drawing speed is 10.5 to 11.5 m / s; When 0.7% < σ ≤ 1.1%, the number of drawing passes is 11 to 12, the deformation per single drawing pass is ≤ 16%, and the wire drawing speed is 10.0 to 11.0 m / s.

[0008] As a further improvement to one embodiment, in the wet drawing process, when σ≤0.3%, the number of drawing passes is 24~26, the deformation of a single drawing pass is ≤16%, the wire drawing speed is (17.5-700σ)m / s~(18.5-700σ)m / s, and the angle of the working cone is 14~16°. When 0.3% < σ ≤ 0.7%, the number of drawing passes is 26 to 28, the deformation per drawing pass is ≤ 15%, the drawing speed is (15.5-300σ) m / s to (16.5-300σ) m / s, and the angle of the working cone is 11 to 13°. When 0.7% < σ ≤ 1.1%, the number of drawing passes is 28 to 30, the deformation per pass is ≤ 14%, the drawing speed is (13.5-200σ) m / s to (14.5-200σ) m / s, and the angle of the working cone is 8 to 10°.

[0009] As a further improvement to one embodiment, in the twisting process, the steel wire after the wet drawing process is twisted into multiple strands. When σ≤0.3%, the tension of the steel wire during twisting is controlled to be 8~12% of the breaking tensile force, the twist pitch is 12~15 times the diameter of the steel wire, the twisting speed is 2300~3500rpm, and the overtwist compensation coefficient is 1.01~1.03; When 0.3% < σ ≤ 0.7%, the tension of the steel wire during twisting should be 6 to 10% of the breaking tensile force, the twist pitch should be 15 to 18 times the diameter of the steel wire, the twisting speed should be 2000 to 3000 rpm, and the overtwist compensation coefficient should be 1.04 to 1.07. When 0.7% < σ ≤ 1.1%, the tension of the steel wire during twisting should be controlled to be 5~8% of the breaking tensile force, the twist pitch should be 18~20 times the diameter of the steel wire, the twisting speed should be 1500~2500 rpm, and the overtwist compensation coefficient should be 1.08~1.10.

[0010] As a further improvement to one embodiment, in the brass plating process, the copper plating electrolyte is an acidic sulfate copper plating electrolyte with a copper sulfate concentration of 180~220 g / L and a current density of 2.5~4.0 A / dm³. 2 The zinc plating electrolyte is an alkaline zincate zinc plating electrolyte with a zinc oxide concentration of 10~15 g / L and a current density of 1.5~2.5 A / dm³. 2 .

[0011] As a further improvement to one embodiment, the brass plating layer of the steel wire obtained by the brass plating process has a copper mass percentage of 61-66%.

[0012] As a further improvement to one embodiment, the diameter of the steel wire obtained in the rough drawing process is 2.8~3.2mm, the diameter of the steel wire obtained in the intermediate drawing process is 1.4~1.8mm, and the diameter of the steel wire obtained in the wet drawing process is 0.175~0.35mm.

[0013] As a further improvement to one embodiment, in the mechanical peeling process, the wire rod is passed through a bending roller group and a reverse bending roller group in sequence, and then a rotating wire brush is used to brush the surface of the wire rod to remove the oxide scale on the surface of the wire rod.

[0014] To achieve the above objectives, one embodiment provides a steel cord prepared using the aforementioned production method.

[0015] Compared with the prior art, the beneficial effects of this application are as follows: This application proposes a residual element factor σ based on the chemical composition of high-carbon steel wire rod, and controls production processes and parameters according to this factor. In the heat treatment process, the heating temperature, holding time, lead bath temperature, and lead bath time are controlled based on the residual element factor σ. The aim is to compensate for the differences in the effects of residual elements such as Cu, Ni, and Cr on the stability of supercooled austenite and the transformation kinetics of pearlite. The higher the σ value, the more severe the segregation of residual elements and the stronger the austenite stability. Therefore, it is necessary to increase the heating temperature and lead bath temperature, and extend the holding time and lead bath time to promote the full solid solution and uniform diffusion of alloying elements, ensuring a fine and uniform sorbite structure after the isothermal transformation in the lead bath, and avoiding abnormal... The precipitation of microstructures such as martensite, bainite, and network cementite ensures that the steel wire possesses both high strength and good plasticity, improving the stability of subsequent drawing and twisting performance. In the brass plating process, as the residual element factor σ increases, increasing the temperature during thermal diffusion can accelerate the mutual diffusion of copper and zinc atoms at the interface, thereby forming a stable and uniform brass coating. This counteracts the adverse effects of residual elements accumulating at the interface of the steel wire substrate, hindering diffusion, and maintaining the copper content in the coating within the target range. Simultaneously, by controlling the thermal diffusion time, it is possible to avoid the decrease in the strength of the steel wire substrate and surface decarburization caused by excessively high temperatures, thereby improving the adhesion between the coating and the substrate and enhancing the bonding performance between the steel cord and rubber. Detailed Implementation

[0016] The present invention will now be described in detail with reference to specific embodiments. However, these embodiments do not limit the present invention, and any structural, methodological, or functional modifications made by those skilled in the art based on these embodiments are included within the scope of protection of the present invention.

[0017] One embodiment of this application provides a method for producing steel cord, which includes sequentially performing mechanical peeling, rough drawing, intermediate drawing, heat treatment, brass plating, wet drawing, and stranding processes. In other words, in this production method, the steel cord is prepared from high-carbon steel wire rod through a series of mechanical peeling, rough drawing, intermediate drawing, heat treatment, brass plating, wet drawing, and stranding processes. Furthermore, one embodiment also provides a steel cord prepared based on this production method.

[0018] High-carbon steel wire rod is produced by electric arc furnace smelting. It is understandable that electric arc furnace smelting uses a large proportion of scrap steel as raw material. The residual elements such as Cu, Ni, Cr, Sn, Sb, and As brought in by the scrap steel are difficult to remove during the steelmaking process and end up remaining in the wire rod, which makes it easy for the wire to break when it is further produced into steel cord.

[0019] In view of this, this application specifically proposes a method for producing the steel cord.

[0020] The chemical composition of high-carbon steel wire rod, by mass percentage, includes: C 0.68~0.86%, Si 0.10~0.30%, Mn 0.30~0.60%, S≤0.015%, P≤0.020%, Al≤0.005%, O≤0.003%, N≤0.005%, Cu≤0.35%, Ni≤0.30%, Cr≤0.30%, Mo≤0.015%, Sn≤0.015%, Sb≤0.015%, As≤0.015%, with the remainder being Fe and unavoidable impurities.

[0021] Among them, the residual element factor σ≤1.1%, σ=Cu+Ni+3(Cr+Mo+Sn)+15N+0.5(Sb+As).

[0022] It is understandable that the chemical composition of the steel cord prepared by further drawing from the high-carbon steel wire rod is consistent with that of the high-carbon steel wire rod, and will not be elaborated further here.

[0023] The roles of each chemical element are explained below.

[0024] Carbon: Carbon is the core element for achieving high strength in steel cord. Through solid solution strengthening and pearlite lamellar strengthening, it ensures that the steel cord has sufficient tensile strength and fatigue resistance when subjected to repeated tire loads. However, excessive carbon content can lead to insufficient pearlite lamellar spacing and increased cementite brittleness, resulting in insufficient wire plasticity during wet drawing and twisting, and a sharp increase in wire breakage rate. At the same time, excessive carbon can easily precipitate network cementite, which deteriorates the bending toughness of the steel cord and affects its reliability under dynamic tire bending conditions.

[0025] Silicon (Si) acts as a ferrite strengthening element, dissolving in the ferrite lamellars of pearlite to improve strength. Simultaneously, as a strong deoxidizer, it reduces oxide inclusions in steel, facilitating a clean matrix and minimizing crack initiation caused by inclusions during drawing. However, excessive Si content significantly reduces material plasticity and toughness, and easily forms brittle silicate inclusions, inducing microcracks during twisting.

[0026] Manganese: Manganese is a cementite strengthening element and a pearlite refining element, which can effectively improve the tensile strength and torsional properties of steel cord. At the same time, Mn combines with S to form MnS, fixing harmful S as plastic inclusions and reducing the tendency of steel cord to become hot brittle and break during drawing. However, Mn increases the hardenability of steel. If the content is too high, abnormal structures such as bainite and martensite can be generated during cooling or heat treatment. These structures will cause uneven deformation during subsequent wet drawing due to differences in hardness and plasticity, resulting in fluctuations in the strength of steel cord and a decrease in fatigue life.

[0027] Sulfur, phosphorus, aluminum, oxygen, and nitrogen are considered harmful elements in this application. Sulfur readily forms sulfides, and if their morphology and distribution are improper, they can easily elongate into strips along the deformation direction during drawing into fine filaments, becoming a cause of steel cord breakage and delamination. Furthermore, sulfur increases hot brittleness, potentially causing surface defects during heat treatment or hot-dip brass plating. Phosphorus (P) segregates at grain boundaries, severely reducing the low-temperature toughness and impact resistance of steel cords, while also increasing the tendency for cold brittleness, leading to brittle fracture during stranding. Al and oxygen (O) are the main elements forming hard, non-deformable inclusions (such as Al₂O₃). These inclusions have high hardness and cannot deform in tandem with the matrix during wet drawing, causing stress concentration around the inclusions, inducing micropores and cracks, significantly reducing the number of torsion cycles and fatigue life of the steel cord, and is also one of the main reasons for increased wire breakage rate. Nitrogen readily forms nitride precipitates with Al, Ti, etc., causing age hardening, which reduces the plasticity of wire rods during storage or processing and increases the brittleness of steel cord during drawing. At the same time, nitride inclusions also impair the fatigue resistance of steel cord.

[0028] Copper, nickel, chromium, molybdenum, tin, antimony, and arsenic are all harmful residual elements in this application. Copper brittleness defects generated during the early hot rolling stage of the wire rod can be inherited by subsequent fine wires. Simultaneously, Cu tends to accumulate at grain boundaries in the steel wire matrix, reducing grain boundary toughness. When steel cord is subjected to tension and torsion during wet drawing and twisting, it is highly susceptible to cracking along Cu-rich grain boundaries. Nickel significantly improves hardenability; if heat treatment is not properly controlled in the final steel cord, it can easily form abnormally hard phases such as bainite or martensite. These hard phases induce localized stress concentration during bending or torsion, leading to brittle fracture. Chromium significantly increases strength and hardness in steel cord but worsens the balance of ductility and toughness. Cr improves hardenability, making it difficult to control the uniformity of the microstructure after heat treatment, easily leading to fluctuations in the strength of the same wire in the steel cord. Even trace amounts of Mo can significantly delay the pearlite transformation, easily leading to uneven microstructure in the final steel cord after heat treatment. Furthermore, Mo increases strength but reduces ductility and toughness, making the steel cord prone to brittle fracture during twisting. Mo also increases the complexity of the brass plating process and affects the compositional uniformity of the copper-zinc alloy coating. Sn, Sb, and As: These elements are prone to segregation at grain boundaries, severely weakening the grain boundary bonding force. This not only exacerbates the hot brittleness and temper brittleness of steel cords, but also induces brittle fracture at grain boundaries under low temperature or dynamic loads, directly leading to frequent wire breakage during drawing and insufficient toughness of the finished steel cords.

[0029] This application introduces a residual element factor σ = Cu + Ni + 3(Cr + Mo + Sn) + 15N + 0.5(Sb + As) to comprehensively evaluate the combined harmful effects of residual elements on the performance of steel cord. Studies have found that as the residual element factor σ increases, the harmful effects of residual elements such as Cu, Ni, Cr, and Sn, including grain boundary segregation, increased hot brittleness, and increased hardenability, are significantly amplified. This leads to a decrease in the plasticity of the steel cord during ultra-fine diameter drawing, a sharp increase in its sensitivity to deformation stress, and a significant increase in the wire breakage rate. Controlling σ to ≤1.1% can effectively ensure the processing stability of the steel cord during multi-pass drawing and twisting processes, ensuring that the final product has excellent comprehensive mechanical properties and service life.

[0030] The following describes each step of the production method of steel cord according to a preferred embodiment of this application.

[0031] (1) Mechanical peeling process The wire rod is passed through the bending roller group and the reverse bending roller group in sequence. Then, a rotating wire brush is used to brush the surface of the wire rod to remove the oxide scale on the surface of the wire rod, so as to avoid the oxide scale scratching the wire or embedding into the surface of the wire during subsequent drawing.

[0032] The diameter of the high-carbon steel wire rod is 5.5~6.5mm.

[0033] Specifically, the wire rod is passed through three sets of bending rollers and three sets of reverse bending rollers in sequence. The oxide scale on the surface of the wire rod is broken up by repeated bending. Then, a pair of rotating wire brushes are used to brush the surface of the wire rod to remove the oxide scale.

[0034] After mechanical descaling, the oxide scale removal rate on the surface of the wire rod is ≥98%, providing a clean surface for subsequent drawing.

[0035] (2) Rough drawing process High-carbon steel wire rods are drawn into steel wires with a diameter of 2.8~3.2mm using a dry drawing process. Dry drawing refers to the use of lubricating powder without the addition of lubricating fluid during the drawing process.

[0036] In one embodiment, when σ≤0.3%, the number of drawing passes is 6 to 7, the deformation per drawing pass is ≤21%, and the wire drawing speed is 7.0 to 8.0 m / s; When 0.3% < σ ≤ 0.7%, the number of drawing passes is 8 to 9, the deformation per single drawing pass is ≤ 19%, and the drawing speed is 5.5 to 6.5 m / s; When 0.7% < σ ≤ 1.1%, the number of drawing passes is 10 to 11, the deformation per single drawing pass is ≤ 17%, and the wire drawing speed is 4.5 to 5.0 m / s.

[0037] Thus, by controlling the parameters in the rough drawing process according to the residual element factor σ, as the content of the residual element factor σ increases, the processing stress can be effectively dispersed by increasing the number of drawing passes, reducing the deformation of a single drawing pass, and reducing the drawing speed, thus avoiding cumulative cracking caused by insufficient plasticity of the wire rod.

[0038] (3) Middle drawing process Dry drawing is used to draw the rough-drawn steel wire into steel wires with a diameter of 1.4~1.8mm.

[0039] When σ≤0.3%, the number of drawing passes is 7~8, the deformation per drawing pass is ≤20%, and the drawing speed is 12.0~13.0m / s; When 0.3% < σ ≤ 0.7%, the number of drawing passes is 9 to 10, the deformation per single drawing pass is ≤ 18%, and the wire drawing speed is 10.5 to 11.5 m / s; When 0.7% < σ ≤ 1.1%, the number of drawing passes is 11 to 12, the deformation per single drawing pass is ≤ 16%, and the wire drawing speed is 10.0 to 11.0 m / s.

[0040] Because the steel wire has already undergone work hardening during rough drawing, it still retains a certain degree of plasticity, thus increasing the drawing speed during intermediate drawing. Furthermore, with the increase in the residual element factor σ content, by increasing the number of drawing passes, reducing the deformation per pass, and decreasing the drawing speed, the processing stress can be effectively dispersed, avoiding cumulative cracking caused by insufficient plasticity of the wire rod.

[0041] (4) Heat treatment process The steel wire obtained from the intermediate drawing process is heated and held at a certain temperature to transform its microstructure into austenitic microstructure. Then, it undergoes a lead bath, which involves placing the steel wire in molten lead to perform an isothermal transformation, causing the austenite to decompose into sorbite at a constant temperature.

[0042] When σ ≤ 0.3%, the heating temperature is (895 + 3000σ)℃ ~ (905 + 3000σ)℃, the holding time is (32 + 2000σ)s ~ (38 + 2000σ)s, the lead bath temperature is (525 + 3000σ)℃ ~ (535 + 3000σ)℃, and the lead bath time is (62 + 2000σ)s ~ (68 + 2000σ)s; when 0.3% < σ ≤ 0.7%, the heating temperature is (905 + 1500σ)℃ ~ (915 + 1500σ)℃, and the holding time is (38 + 1000σ)s ~ (43 + 1 When the lead bath temperature is (535+1500σ)℃~(545+1500σ)℃ and the lead bath time is (68+1500σ)s~(73+1500σ)s; when 0.7%<σ≤1.1%, the heating temperature is (915+1000σ)℃~(925+1000σ)℃, the holding time is (43+500σ)s~(48+500σ)s, the lead bath temperature is (545+1000σ)℃~(555+1000σ)℃, and the lead bath time is (73+1000σ)s~(78+1000σ)s.

[0043] Due to the accumulation of dislocations and stresses within the steel wire after intermediate drawing, its plasticity deteriorates. Heat treatment can eliminate work hardening and restore plasticity. During the heat treatment process, the heating temperature, holding time, lead bath temperature, and lead bath time are controlled according to the residual element factor σ. This aims to compensate for the differences in the effects of residual elements such as Cu, Ni, and Cr on the stability of supercooled austenite and the transformation kinetics of pearlite. A higher σ value indicates more severe segregation of residual elements and stronger austenite stability. Therefore, it is necessary to increase the heating temperature and lead bath temperature, and extend the holding time and lead bath time to promote sufficient solid solution and uniform diffusion of alloying elements. This ensures a fine and uniform sorbite structure after the isothermal transformation in the lead bath, avoiding the precipitation of abnormal structures such as martensite, bainite, and network cementite. This guarantees that the steel wire possesses both high strength and good plasticity, improving the stability of subsequent drawing and twisting performance.

[0044] (5) Brass plating process The steel wire that has undergone the heat treatment process is then subjected to copper plating, zinc plating, and thermal diffusion to obtain a steel wire with a brass plating layer.

[0045] The heat diffusion time is 10~25s; when σ≤0.3%, the temperature for controlling heat diffusion is 540~550℃; when 0.3%<σ≤0.7%, the temperature for controlling heat diffusion is 550~560℃; when 0.7%<σ≤1.1%, the temperature for controlling heat diffusion is 560~570℃; and the heat diffusion time is 10~25s.

[0046] The higher the residual element factor σ, the more sensitive the steel wire is to thermal stress. By controlling the temperature during thermal diffusion based on the residual element factor σ, the deformation capacity of steel wires in different plastic states can be matched, preventing brittle fracture induced by thermal or torsional stress.

[0047] As the residual element factor σ increases, increasing the temperature during thermal diffusion can accelerate the diffusion of copper and zinc atoms at the interface, thereby forming a stable and uniform brass coating. This counteracts the adverse effects of residual elements accumulating at the steel wire substrate interface and hindering diffusion, keeping the copper content in the coating within the target range. Simultaneously, by controlling the thermal diffusion time, it is possible to avoid the decrease in the strength of the steel wire substrate and surface decarburization caused by excessively high temperatures, thereby improving the adhesion between the coating and the substrate and enhancing the bonding performance between the steel cord and rubber.

[0048] In one embodiment, the copper plating electrolyte is an acidic sulfate copper plating electrolyte, wherein the concentration of copper sulfate in the copper plating electrolyte is 180~220 g / L, and the current density is 2.5~4.0 A / dm³. 2 The zinc plating electrolyte is an alkaline zincate zinc plating electrolyte with a zinc oxide concentration of 10~15 g / L and a current density of 1.5~2.5 A / dm³. 2 .

[0049] In one embodiment, the brass plating layer of the steel wire obtained by the brass plating process has a copper mass percentage of 61-66%.

[0050] (6) Wet drawing process Wet drawing is a process in which steel wire is drawn at high speed with lubricant in a water tank wire drawing machine. The diameter of the steel wire obtained by the wet drawing process is 0.175~0.35mm.

[0051] When σ≤0.3%, the number of drawing passes should be controlled at 24~26, the deformation of a single drawing pass should be ≤16%, the drawing speed should be (17.5-700σ)m / s~(18.5-700σ)m / s, and the angle of the working cone should be 14~16°. When 0.3% < σ ≤ 0.7%, the number of drawing passes should be controlled at 26 to 28, the deformation of a single drawing pass should be ≤ 15%, the drawing speed should be (15.5-300σ) m / s to (16.5-300σ) m / s, and the angle of the working cone should be 11 to 13°. When 0.7% < σ ≤ 1.1%, the number of drawing passes should be controlled at 28 to 30, the deformation per drawing pass should be ≤ 14%, the drawing speed should be (13.5-200σ) m / s to (14.5-200σ) m / s, and the angle of the working cone should be 8 to 10°.

[0052] The working cone angle refers to the opening angle of the conical flare at the entrance of the wire drawing die. The smaller the working cone angle, the smoother the metal flow, but the longer the friction stroke.

[0053] The higher the residual element factor σ, the more significant the work hardening and brittleness tendency of the steel wire. As the residual element factor σ increases, by increasing the number of drawing passes, reducing the deformation amount per drawing pass, reducing the wire drawing speed, and reducing the working cone angle, the deformation heat and drawing stress of each pass can be reduced. This avoids the steel wire from losing plasticity or developing internal cracks due to excessive cumulative strain, making the deformation more gentle and reducing concentrated shear stress. A gentler deformation path can ensure the integrity of the lubricating film on the steel wire surface and controllable temperature rise, thereby ensuring the deformation uniformity and surface quality of small diameter steel wire in high-speed, multi-pass drawing processes, effectively reducing the wire breakage rate, and ensuring the continuous and stable production of small diameter steel wire.

[0054] (7) Twisting process The steel wires after the wet drawing process are twisted into multiple strands to produce steel cord.

[0055] When σ≤0.3%, the tension of the steel wire during twisting is controlled to be 8~12% of the breaking tensile force, the twist pitch is 12~15 times the diameter of the steel wire, the twisting speed is 2300~3500rpm, and the overtwist compensation coefficient is 1.01~1.03; When 0.3% < σ ≤ 0.7%, the tension of the steel wire during twisting should be 6 to 10% of the breaking tensile force, the twist pitch should be 15 to 18 times the diameter of the steel wire, the twisting speed should be 2000 to 3000 rpm, and the overtwist compensation coefficient should be 1.04 to 1.07. When 0.7% < σ ≤ 1.1%, the tension of the steel wire during twisting should be controlled to be 5~8% of the breaking tensile force, the twist pitch should be 18~20 times the diameter of the steel wire, the twisting speed should be 1500~2500 rpm, and the overtwist compensation coefficient should be 1.08~1.10.

[0056] As the residual element factor σ increases, the plasticity of the steel wire deteriorates. By controlling the tension to decrease, wire breakage during twisting can be avoided. By controlling the lay length to increase, torsional stress can be reduced. By controlling the twisting parameters according to the residual element factor σ, the deformation capacity of steel wires under different plastic states can be matched, preventing brittle fracture induced by thermal or torsional stress.

[0057] Because the steel wire will spring back after twisting, i.e., untwist, it needs to be slightly over-twisted before springing back to the target value. As the residual element factor σ increases, the plasticity of the steel wire deteriorates, and the springback increases, so the compensation coefficient needs to be increased.

[0058] The wire breakage rate of steel cord during the production process is ≤2 times / ton.

[0059] One embodiment of this application also provides a high-carbon steel wire rod and a method for producing the same, wherein the steel cord is prepared using the high-carbon steel wire rod as the base material.

[0060] The production method of this high-carbon steel wire rod includes the sequential processes of electric furnace smelting, LF refining, continuous casting, high-speed wire rolling, and Stellmore cooling.

[0061] The following describes each step of the production method of high-carbon steel wire rod according to a preferred embodiment of this application.

[0062] (a) Electric furnace smelting process The electric furnace smelting process is carried out in an electric furnace.

[0063] The raw materials for the electric furnace smelting process include scrap steel, which accounts for 40-100% of the total mass of the raw materials.

[0064] Among them, scrap steel refers to scrap steel such as head and tail billets, trimmed scrap, rolling scrap, and casting residue generated during the steel production process, as well as processing scrap generated during machining and other processes, and recycled scrap steel that has been sorted and packaged, but it is not limited to these.

[0065] The smelting raw materials also include molten iron.

[0066] It is understood that the percentage of scrap steel in the smelting raw materials refers to the percentage of the mass of scrap steel added to the electric furnace in the molten steel mixture made by adding molten iron and scrap steel.

[0067] (ii) LF refining process The molten steel obtained from the electric arc furnace smelting process is sent to the LF furnace for refining in order to adjust the chemical composition and inclusions.

[0068] Specifically, when molten steel arrives at the LF furnace, its temperature is measured and sampled. Then, it is heated by electricity to adjust the temperature of the molten steel. Then, based on the chemical composition measured by the sample taken at the furnace, alloys and carbon powder are added to carry out alloying. After that, slag-forming materials are added to the molten steel to form slag.

[0069] The chemical composition of the molten steel obtained from the LF refining process, by mass percentage, includes: C 0.68~0.86%, Si 0.10~0.30%, Mn 0.30~0.60%, S≤0.015%, P≤0.020%, Al≤0.005%, O≤0.003%, N≤0.005%, Cu≤0.35%, Ni≤0.30%, Cr≤0.30%, Mo≤0.015%, Sn≤0.015%, Sb≤0.015%, As≤0.015%, with the remainder being Fe and unavoidable impurities.

[0070] Among them, the residual element factor σ ≤ 1.1%.

[0071] σ = Cu + Ni + 3(Cr + Mo + Sn) + 15N + 0.5(Sb + As). The symbols for each element in the formula represent the corresponding mass percentage. For example, if the mass percentage of Cu is 0.68%, then 0.68% is substituted into the formula for Cu in the calculation. The same logic applies to other elements, and will not be elaborated further.

[0072] It is understandable that the chemical composition of the continuously cast billets obtained in the subsequent continuous casting process, as well as the chemical composition of the final wire rod, are roughly the same as the chemical composition of the molten steel obtained in the LF refining process, which will not be elaborated on later.

[0073] Carbon (C) is a core solid solution strengthening element in steel, ensuring the high strength of the wire rod. As the C content increases, the strength and hardness of the steel increase, while its plasticity and toughness decrease. In this application, the C content is controlled at 0.68~0.86%, which can make full use of the strengthening effect of carbon while avoiding the formation of network cementite and the reduction of wire rod drawing performance caused by excessive carbon content.

[0074] Silicon (Si) is a ferrite-strengthening element that can dissolve in the ferrite lamellars of pearlite, thereby improving the strength of steel. Si is also an important deoxidizer, helping to reduce the oxygen content in steel and reduce inclusions. However, excessive Si content will reduce the plasticity and toughness of steel and easily form brittle silicate inclusions, hindering subsequent drawing processes. Therefore, this application controls the Si content to be between 0.10% and 0.30%.

[0075] Manganese (Mn): As a cementite strengthening element, Mn can improve the strength of cementite and refine the pearlite lamellars, thereby increasing the strength of wire rod. Mn is also a good deoxidizer; it can combine with sulfur (S) to form manganese sulfide, eliminating the harmful effects of S in steel and reducing hot brittleness. However, excessive Mn content can easily lead to low-temperature microstructure and reduce the drawing performance of wire rod. In this application, the Mn content is controlled at 0.30~0.60%.

[0076] Sulfur, phosphorus, aluminum, oxygen, and nitrogen are considered harmful elements in this application. S readily forms MnS inclusions, leading to hot brittleness in steel and reducing its plasticity. P readily segregates at grain boundaries, causing cold brittleness and reducing low-temperature toughness. Al and O are the main elements forming hard, non-deformable inclusions such as Al2O3. These inclusions disrupt the continuity of the matrix, becoming stress concentration points and crack initiation sites, significantly reducing the fatigue life and drawability of steel. N readily forms nitrides such as AlN and TiN, leading to age hardening and reducing plasticity. Therefore, this application controls the contents of S, P, Al, O, and N to be S≤0.015%, P≤0.020%, Al≤0.005%, O≤0.003%, and N≤0.005%, respectively.

[0077] Copper, nickel, chromium, molybdenum, tin, antimony, and arsenic are all harmful residual elements in this application, mainly derived from scrap steel, and are difficult to remove effectively during the smelting process. During hot rolling, Cu tends to accumulate on the surface, forming a low-melting-point liquid phase, leading to copper embrittlement and surface cracking. Ni, Cr, and Mo affect the pearlite transformation temperature, significantly increasing the hardenability of steel, making it easy for abnormal structures such as bainite and martensite to form in the wire rod during rolling and cooling. These abnormal structures have high hardness, poor plasticity, and are prone to wire breakage during drawing. Sn, Sb, and As readily accumulate at grain boundaries during the solidification of molten steel and subsequent heat treatment, severely reducing the grain boundary bonding energy. This not only exacerbates hot brittleness but also leads to temper brittleness and low-temperature brittleness, worsening the plasticity and drawing properties of the wire rod. Therefore, this application controls Cu ≤ 0.35%, Ni ≤ 0.30%, Cr ≤ 0.30%, Mo ≤ 0.015%, Sn ≤ 0.015%, Sb ≤ 0.015%, and As ≤ 0.015%.

[0078] (III) Continuous casting process The molten steel obtained from the LF refining process is fed into a continuous casting machine for continuous casting to obtain a square billet with a cross-sectional size of 140mm×140mm~150mm×150mm.

[0079] The continuous casting machine includes a rotary table, tundish, crystallizer, sector section, and straightening machine. The rotary table can rotate 180 degrees, moving the ladle to the pouring position to allow for continuous pouring of multiple heats of molten steel. The tundish, located below the ladle, serves as a crucial transition vessel, buffering the molten steel, stabilizing the flow rate, and providing time for impurities such as slag to rise and purify the steel. The crystallizer cools the billet initially, causing it to solidify and form a shell. The sector section supports and further cools the billet exiting the crystallizer. The straightening machine pulls out and straightens the billet.

[0080] The fan-shaped section forms the secondary cooling zone in the continuous casting process, meaning that the billet undergoes secondary cooling in this zone. The solidification end is part of this secondary cooling zone. This secondary cooling zone employs a four-zone water mist cooling system.

[0081] The straightening machine forms the straightening zone in the continuous casting process.

[0082] The superheat of the molten steel during casting is controlled at 20~26℃; the continuous casting speed v is (2.6-50σ)min~(2.8-50σ)min; the specific water volume Q in the secondary cooling zone is (1.5-50σ)L / kg~(1.7-50σ)L / kg; light reduction is adopted at the end of solidification, and the total reduction D is (3.0+500σ)mm~(4.0+500σ)mm; the inlet temperature of the straightening zone is >930℃.

[0083] In other words, the casting speed v and total reduction D are adjusted based on the residual element factor σ. As σ increases, the casting speed is reduced, thereby prolonging the solidification time of molten steel in the crystallizer and secondary cooling zone, allowing the molten steel to solidify fully and the composition to diffuse evenly, reducing central segregation and porosity. As σ increases, the total reduction is appropriately increased, which can further compact the porosity and segregation zone at the end of solidification, reduce central shrinkage cavities and porosity defects, and improve the density of the billet.

[0084] Adjusting the specific water volume Q in the secondary cooling zone based on the residual element factor σ can achieve uniform cooling and avoid thermal stress caused by sudden cooling of the billet surface. As σ increases, the specific water volume is reduced to accommodate the embrittlement risk caused by residual element segregation. This ensures rapid solidification of the continuously cast billet to suppress segregation and avoids surface cracks and corner cracks caused by excessive cooling intensity. Combined with the inlet temperature control of the straightening zone, the continuously cast billet can be straightened in the high-temperature plastic zone, reducing straightening cracks.

[0085] In summary, by controlling the superheat of molten steel, we can ensure its fluidity, prevent nozzle blockage, and prevent excessive superheat from causing coarse grains and increased segregation. Furthermore, by controlling the continuous casting speed, the specific water volume in the secondary cooling zone, and the reduction at the solidification end based on the residual element factor σ, we can control the solidification time of molten steel in the crystallizer and secondary cooling zone, and ensure uniform cooling. This avoids thermal stress caused by sudden cooling of the continuous casting billet surface, allowing the molten steel to solidify fully and the composition to diffuse evenly, reducing central segregation and porosity. At the same time, by controlling the light reduction, we can further compact the porosity and segregation zone at the solidification end, reduce central shrinkage cavities and porosity defects, improve the density of the continuous casting billet, and thus improve the internal quality of the continuous casting billet.

[0086] In a preferred embodiment, dynamic light reduction is employed at the solidification end. Dynamic light reduction refers to tracking the position of the solidification end of the continuously cast billet in real time during the continuous casting process and applying light reduction to the billet based on the tracked solidification end position. This allows for real-time calculation and dynamic adjustment during continuous casting, proactively compensating for the volume shrinkage of the billet at the end of solidification, effectively preventing central porosity and shrinkage cavities. Furthermore, light reduction can push the molten steel enriched with segregated elements in the pasty region of the billet back upstream, preventing it from ultimately solidifying in the center, thereby significantly reducing central segregation.

[0087] In a preferred embodiment, when σ≤0.3%, the superheat of the molten steel during casting is controlled to be 24~26℃; When 0.3% < σ ≤ 0.7%, the superheat of the molten steel during casting should be controlled at 22~24℃; When 0.7% < σ ≤ 1.1%, the superheat of the molten steel during casting should be controlled at 20~22℃.

[0088] When σ ≤ 0.3%, the compositional uniformity of the molten steel is good. A superheat of 24~26℃ is used to ensure the fluidity of the molten steel, prevent nozzle blockage, and prevent excessive superheating from causing coarse grains and increased segregation. As σ increases, the superheat needs to be appropriately reduced. This shortens the solidification time of the molten steel, reduces the enrichment of residual elements at grain boundaries, inhibits central segregation and grain boundary embrittlement, and avoids insufficient fluidity due to excessive superheating, thus preventing cold shut defects in the continuously cast billet. Cold shut defects refer to the gap-like interface defects formed when two or more streams of molten steel with lower temperatures meet during continuous casting, resulting in an interface temperature below the liquidus line and incomplete fusion.

[0089] In a preferred embodiment, the electromagnetic stirring current in the crystallizer is 310~390A and the frequency is 3.8~4.6Hz; the electromagnetic stirring current at the solidification end is 380~520A and the frequency is 3.8~5.2Hz. By performing electromagnetic stirring in the crystallizer and at the solidification end, the two work synergistically to refine the grains, promote the flotation of inclusions, and reduce segregation.

[0090] In a preferred embodiment, when σ≤0.3%, the electromagnetic stirring current of the crystallizer is controlled to be 310~330A and the frequency is 3.8~4.0Hz, and the electromagnetic stirring current at the end of solidification is 380~420A and the frequency is 3.8~4.2Hz. When 0.3% < σ ≤ 0.7%, the electromagnetic stirring current of the crystallizer is controlled at 340~360A and the frequency is 4.1~4.3Hz, and the electromagnetic stirring current at the end of solidification is 430~470A and the frequency is 4.3~4.7Hz. When 0.7% < σ ≤ 1.1%, the electromagnetic stirring current of the crystallizer is controlled at 370~390A and the frequency is 4.4~4.6Hz, and the electromagnetic stirring current at the end of solidification is 480~520A and the frequency is 4.8~5.2Hz.

[0091] Thus, when σ≤0.3%, the compositional uniformity of the molten steel is good, and the grain refinement effect can be achieved using a relatively low electromagnetic stirring intensity. However, as σ increases, it is necessary to appropriately increase the electromagnetic stirring current and frequency to enhance the electromagnetic stirring intensity, break the grain boundary enrichment trend of residual elements, refine the grain structure, reduce the formation of abnormal structures such as martensite, and improve the toughness and plasticity of the continuously cast billet.

[0092] In a preferred embodiment, when σ≤0.3%, the inlet temperature of the straightening zone is controlled to be >930℃; When 0.3% < σ ≤ 0.7%, control the inlet temperature of the straightening zone to be > 950℃; When 0.7% < σ ≤ 1.1%, the inlet temperature of the straightening zone should be controlled to be > 980℃.

[0093] Thus, when σ≤0.3%, controlling the inlet temperature of the straightening zone to >930℃ allows the continuously cast billet to be straightened in a region with good high-temperature plasticity, avoiding cracks caused by cold straightening. As σ increases, the straightening temperature needs to be increased to improve the plasticity of the continuously cast billet, offset the embrittlement effect caused by residual element segregation, and effectively prevent surface and internal cracks from occurring during the straightening process.

[0094] (iv) High-speed wire rod rolling process The continuously cast billet obtained from the continuous casting process is heated and then rolled. The soaking temperature during heating is 1060~1140℃, the soaking time is 20~40min, the initial rolling temperature is 980~1040℃, and the wire drawing temperature is (880+3000σ)℃~(890+3000σ)℃. The heating is carried out in a heating furnace.

[0095] By controlling the heating temperature, time, and initial rolling temperature, and by controlling the wire drawing temperature based on the residual element factor σ, the pearlite phase transformation process can be controlled, the precipitation of network cementite can be suppressed, the harm of residual elements can be reduced, and the strength and drawing performance of the final wire rod can be improved.

[0096] In a preferred embodiment, when σ≤0.3%, the temperature of the soaking zone during heating is 1100~1140℃, the soaking time is 30~40min, and the initial rolling temperature is 1020~1040℃; When 0.3% < σ ≤ 0.7%, the temperature of the soaking zone during heating is 1080~1120℃, the soaking time is 25~35min, and the initial rolling temperature is 1000~1020℃; When 0.7% < σ ≤ 1.1%, the temperature of the soaking zone during heating is 1060~1100℃, the soaking time is 20~30min, and the initial rolling temperature is 980~1000℃.

[0097] Thus, by controlling the temperature of the soaking zone, the soaking time, and the initial rolling temperature during heating according to the residual element factor σ, it is possible to prevent the aggravation of surface decarburization and grain boundary oxidation caused by prolonged high-temperature heating, and to inhibit the enrichment of residual elements at the austenite grain boundaries and the surface of the billet, laying a good foundation for subsequent rolling and phase transformation control.

[0098] In a preferred embodiment, the heating furnace employs a reducing atmosphere with an air-fuel ratio of 0.7 to 0.9, and maintains a slight positive pressure within the furnace chamber at 10 to 30 Pa. A reducing atmosphere refers to a low-oxygen content, rich in reducing gases such as carbon monoxide (CO) and hydrogen (H2). By controlling the incomplete combustion at an air-fuel ratio of 0.7 to 0.9 and isolating the furnace from external air at a slight positive pressure of 10 to 30 Pa, a CO-rich and O2-low flue gas environment is created within the furnace chamber, thereby suppressing surface oxidation and decarburization during the heating of high-carbon steel wire rod.

[0099] This can prevent the intensification of surface decarburization and grain boundary oxidation caused by prolonged high-temperature heating, inhibit the enrichment of residual elements on the austenite grain boundaries and the surface of the continuously cast billet, and lay a good foundation for subsequent rolling and phase transformation control.

[0100] (v) Stellmore Cooling Process When the temperature T≥700°C, the cooling rate is controlled as ν1, and ν1 is (16-500σ)°C / s to (18-500σ)°C / s; when 500°C<T<700°C, the cooling rate is controlled as ν2, and ν2 is (12.5-500σ)°C / s to (13.5-500σ)°C / s; when T≤500°C, the cooling rate is controlled as ν3, and ν3 is 2 to 6°C / s. In this way, through sectional cooling and controlling the cooling rate based on the residual element factor σ, the pearlite phase transformation process can be controlled, the precipitation of network cementite can be inhibited, and the formation of martensite caused by excessively fast cooling rate can be avoided, so as to obtain a large proportion of sorbite, reduce the harm of residual elements, and improve the strength and drawing performance of the finally obtained wire rod.

[0101] In a preferred embodiment, when σ≤0.3% and the temperature T≤500°C, the controlled cooling rate ν3 is 4~6°C / s; when 0.3%<σ≤0.7% and the temperature T≤500°C, the controlled cooling rate ν3 is 3~5°C / s; when 0.7%<σ≤1.1% and the temperature T≤500°C, the controlled cooling rate ν3 is 2~4°C / s.

[0102] Due to the large amount of residual elements such as Cu, Ni, Cr, and Mo, the transformation of undercooled austenite to pearlite will be significantly delayed, and the tendency to form martensite will be greatly increased. In order to prevent martensite from being formed below 500°C due to excessively fast cooling rate, it is necessary to adjust the cooling rate below 500°C according to the residual element factor σ, so as to avoid the martensite transformation region and prevent the formation of abnormal structures such as martensite structure.

[0103] In conclusion, in the production method of high-carbon steel wire rod according to an embodiment of the present application, the basic strength of the wire rod is ensured by controlling the C content in molten steel after smelting; the balance between high strength and high plasticity is achieved by controlling the content of Si and Mn; the upper limit of the content of harmful impurity elements S, P, Al, O and N is controlled to improve the cleanliness of molten steel and reduce the tendency of brittle inclusions and aging embrittlement from the source; by introducing the residual element factor σ, different residual elements are weighted and quantified, and the relationship between various parameters in the continuous casting process, high-speed wire rolling process and Stelmor cooling process and the residual element factor σ is established, which can not only effectively inhibit the segregation of residual elements, reduce defects such as center segregation, porosity, cracks and slag inclusions in continuous casting billets, improve the surface quality and internal structure uniformity of continuous casting billets, and reduce the risk of wire breaking in subsequent rolling and drawing processes, but also can inhibit the grain boundary segregation of residual elements according to the influence of different residual element factors on phase transformation temperature and phase transformation time, so that the wire rod has both high strength and high toughness, meets the requirements of high drawing processing, reduces the risk of wire breaking in subsequent drawing process, thereby reducing the harm of high residual elements caused by a large proportion of scrap steel in smelting raw materials. In this way, electric furnace can be used for smelting, improving production efficiency and reducing carbon emission.

[0104] This application also provides a high-carbon steel wire rod according to one embodiment. This high-carbon steel wire rod can be prepared using the above-described production method.

[0105] The diameter of this high-carbon steel wire rod is 5.5~6.5mm.

[0106] Tests showed that the high-carbon steel wire rod had a tensile strength of 980~1260MPa, a strength difference of ≤25MPa within the same coil, a reduction of area of ​​≥35%, and a wire breakage rate of ≤1 time / t during drawing.

[0107] The wire rod has a microstructure of sorbite + pearlite + ferrite, with a sorbitization rate of ≥85%, a sorbite lamellar spacing of 200~220nm, and a network cementite grade of ≤1.

[0108] This high-carbon steel wire rod combines high strength, high plasticity, and excellent drawing performance, solving the technical problems of high residual element hazards, poor microstructure uniformity, and high wire breakage rate during wire rod production caused by the high proportion of scrap steel when using electric furnace smelting.

[0109] The detailed descriptions listed above are merely specific descriptions of feasible embodiments of the present invention, and are not intended to limit the scope of protection of the present invention. All equivalent embodiments or modifications made without departing from the spirit of the present invention should be included within the scope of protection of the present invention.

[0110] The beneficial effects of the present invention will be further illustrated below through specific embodiments. Of course, these embodiments are only a part of the many variations contained in this application, and not all of them.

[0111] Example 1 The following section describes the various processes involved in the production of high-carbon steel wire rod and steel cord.

[0112] (1) Electric furnace smelting process The electric furnace smelting process is carried out in an electric furnace.

[0113] The raw materials for electric arc furnace smelting include scrap steel and molten iron, with scrap steel accounting for 70% of the raw materials by mass.

[0114] (2) LF refining process The molten steel obtained from the electric arc furnace smelting process is sent to the LF furnace for refining in order to adjust the chemical composition and inclusions.

[0115] Specifically, when molten steel arrives at the LF furnace, its temperature is measured and sampled. Then, it is heated by electricity to adjust the temperature of the molten steel. Then, based on the chemical composition measured by the sample taken at the furnace, alloys and carbon powder are added to carry out alloying. After that, slag-forming materials are added to the molten steel to form slag.

[0116] The chemical composition of the molten steel obtained from the LF refining process, by mass percentage, includes: C 0.68%, Si 0.1%, Mn 0.3%, S 0.010%, P 0.012%, Al 0.002%, O 0.018%, N 0.002%, Cu 0.25%, Ni 0.20%, Cr 0.05%, Mo 0.010%, Sn 0.010%, Sb 0.010%, As 0.010%, with the remainder being Fe and unavoidable impurities.

[0117] The residual element factor σ is 0.7%.

[0118] (3) Continuous casting process The molten steel obtained from the LF refining process is fed into a continuous casting machine for continuous casting to obtain a square billet with a cross-sectional size of 140mm×140mm.

[0119] The continuous casting machine includes a rotary table, tundish, crystallizer, sector section, and straightening machine. The rotary table can rotate 180 degrees, moving the ladle to the pouring position to allow for continuous pouring of multiple heats of molten steel. The tundish, located below the ladle, serves as a crucial transition vessel, buffering the molten steel, stabilizing the flow rate, and providing time for impurities such as slag to rise and purify the steel. The crystallizer cools the billet initially, causing it to solidify and form a shell. The sector section supports and further cools the billet exiting the crystallizer. The straightening machine pulls out and straightens the billet.

[0120] The fan-shaped section forms the secondary cooling zone in the continuous casting process, meaning that the billet undergoes secondary cooling in this zone. The solidification end is part of this secondary cooling zone. This secondary cooling zone employs a four-zone water mist cooling system.

[0121] The straightening machine forms the straightening zone in the continuous casting process.

[0122] The superheat of the molten steel during casting is controlled at 22℃; the electromagnetic stirring current of the crystallizer is controlled at 360A and the frequency at 4.3Hz; the continuous casting speed is v=2.35m / min; the specific water volume in the secondary cooling zone is Q=1.25L / kg; the electromagnetic stirring current at the solidification end is 470A and the frequency is 4.7Hz, and dynamic light reduction is adopted at the solidification end, with a total reduction of D=7mm; the inlet temperature of the straightening zone is 970℃.

[0123] (4) High-speed wire rolling process The continuously cast billet obtained from the continuous casting process is heated and then rolled to obtain wire rod with a diameter of 6.5 mm. Heating is carried out in a heating furnace using a reducing atmosphere, an air-fuel ratio of 0.75, and a slightly positive pressure of 20 Pa within the furnace. The soaking temperature is 1080℃, the soaking time is 25 min, the initial rolling temperature is 1000℃, and the wire drawing temperature is 906℃.

[0124] (5) Stelmor cooling process When the temperature T≥700℃, the controlled cooling rate is 12.5℃ / s; when 500℃<T<700℃, the controlled cooling rate is 9℃ / s; when T≤500℃, the controlled cooling rate is 3℃ / s.

[0125] Structure and performance testing is performed on the wire rod, including: In terms of mechanical properties, sampling and mechanical property testing of the wire rod are carried out by a tensile testing machine in accordance with the standard test method and definition specified in GB / T 2975-2018 *Steel and Steel Products - Location and Preparation of Test Pieces for Mechanical Testing*.

[0126] It is measured that the high-carbon steel wire rod has a tensile strength of 1052MPa, a strength difference within the same coil of 20MPa, a reduction of area of 43%, and a breaking rate during drawing of 0.5 times / t.

[0127] In terms of structure and performance, with reference to GB / T 13298-2025 *Method for Inspection of Microstructure of Metals*, it is measured that the structure of the wire rod is sorbite + pearlite + ferrite, with a sorbite rate of 86%, a sorbite lamellar spacing of 210nm, a network cementite grade of 0, and a martensite grade of 0.

[0128] (6) Mechanical descaling process The wire rod is sequentially passed through 3 sets of bending roller groups and 3 sets of reverse bending roller groups, and then the surface of the wire rod is brushed and ground by a pair of rotating wire brushes.

[0129] After mechanical descaling, the oxide scale removal rate on the surface of the wire rod is 99%.

[0130] (7) Rough drawing process The high-carbon steel wire rod is drawn into a steel wire with a diameter of 2.8mm by dry drawing. The drawing is performed in 7 passes, the deformation per pass is ≤20%, and the drawing speed is 7.5m / s.

[0131] (8) Intermediate drawing process The steel wire after rough drawing is drawn into a steel wire with a diameter of 1.5mm by dry drawing. The drawing is performed in 7 passes, the deformation per pass is ≤18%, and the drawing speed is 12.5m / s.

[0132] (9) Heat treatment process The steel wire obtained from the intermediate drawing process is heated, held for heat preservation, and then subjected to lead bath treatment.

[0133] Wherein, the heating temperature is 920℃, the holding time is 48s, the lead bath temperature is 550℃, and the lead bath time is 81s.

[0134] (10) Brass plating process The steel wire that has undergone the heat treatment process is then subjected to copper plating, zinc plating, and thermal diffusion to obtain a steel wire with a brass plating layer.

[0135] The copper plating electrolyte is an acidic sulfate copper plating electrolyte with a copper sulfate concentration of 200 g / L and a current density of 3.2 A / dm³. 2 The zinc plating electrolyte used is an alkaline zincate zinc plating electrolyte with a zinc oxide concentration of 12.5 g / L and a current density of 2.0 A / dm³. 2 The temperature for controlled thermal diffusion was 545℃, and the thermal diffusion time was 15s.

[0136] The brass coating of the obtained brass-plated steel wire has a copper mass percentage of 63.5%.

[0137] (11) Wet drawing process In a water tank wire drawing machine, steel wire is drawn at high speed with lubricant to obtain a steel wire with a diameter of 0.175mm.

[0138] The drawing process involves 25 passes, with a deformation of ≤15% per pass, a drawing speed of 13.9 m / s, and a working cone angle of 15°.

[0139] (12) Twisting process The steel wires after the wet drawing process are twisted into multiple strands to produce steel cord. During twisting, the tension of the steel wire is controlled to be 10% of the breaking tensile force, the twist pitch is 13 times the diameter of the steel wire, the twisting speed is 2900 rpm, and the overtwist compensation coefficient is 1.02.

[0140] The wire breakage rate of steel cord during the production process is ≤1 break per ton.

[0141] Example 2 The following section describes the various processes involved in the production of high-carbon steel wire rod and steel cord.

[0142] (1) Electric furnace smelting process The electric arc furnace smelting process is carried out in an electric arc furnace. All raw materials used in the smelting are scrap steel, meaning that scrap steel accounts for 100% of the total mass of the raw materials.

[0143] (2) LF refining process The molten steel obtained from the electric furnace smelting process is sent to an LF furnace for refining. The chemical composition of the molten steel obtained from the LF refining process, calculated by mass percentage, comprises: 0.80% of C, 0.20% of Si, 0.50% of Mn, 0.012% of S, 0.015% of P, 0.003% of Al, 0.002% of O, 0.004% of N, 0.30% of Cu, 0.25% of Ni, 0.12% of Cr, 0.012% of Mo, 0.012% of Sn, 0.012% of Sb, 0.012% of As, with the remainder being Fe and unavoidable impurities.

[0144] Wherein, the residual element factor σ is 1.054%.

[0145] (3) Continuous casting process The molten steel obtained from the LF refining process is sent to a continuous caster for continuous casting, so as to obtain a square billet with a cross-sectional dimension of 150 mm × 150 mm.

[0146] The superheat of the molten steel during casting is controlled to be 21°C; the electromagnetic stirring current of the crystallizer is controlled to be 380 A and the frequency is controlled to be 4.5 Hz; the continuous casting drawing speed v = 2.17 m / min; the specific water flow Q in the secondary cooling zone is 1.07 L / kg; the electromagnetic stirring current at the solidification end is 500 A and the frequency is 5.0 Hz. Dynamic soft reduction is adopted at the solidification end, with a total reduction D = 8.8 mm; the inlet temperature of the straightening zone is 990°C.

[0147] (4) High-speed wire rolling process The continuous casting billet obtained from the continuous casting process is heated and then rolled to obtain a wire rod with a diameter of 5.5 mm. The heating is carried out in a heating furnace, the heating furnace adopts a reducing atmosphere with an air-fuel ratio of 0.8, and the interior of the furnace chamber is controlled to have a slight positive pressure of 20 Pa. The temperature of the soaking section during heating is 1080°C, the soaking time is 25 min, the starting rolling temperature is 990°C, and the laying temperature is 917°C.

[0148] (5) Stelmor cooling process When the temperature T ≥ 700°C, the cooling rate is controlled to be 10.7°C / s; when 500°C < T < 700°C, the cooling rate is controlled to be 7.2°C / s; when T ≤ 500°C, the cooling rate is controlled to be 3°C / s.

[0149] The microstructure and properties of the wire rod are tested, which includes: In terms of mechanical properties, sampling and mechanical property test are carried out on the wire rod by a tensile testing machine with reference to the standard test method specified in GB / T 2975-2018 *Steel and Steel Products - Location and Preparation of Test Pieces for Mechanical Testing of Steel Products*.

[0150] The measured values of the high-carbon steel wire rod are as follows: the tensile strength is 1178 MPa, the strength difference within the same coil is 22 MPa, the reduction of area is 39%, and the drawing fracture rate is 0.8 times per ton.

[0151] In terms of microstructure and properties, referring to GB / T 13298-2025 "Methods for Testing the Microstructure of Metals", the microstructure of the wire rod was measured to be sorbite + pearlite + ferrite, with a sorbitization rate of 88%, a sorbite lamellar spacing of 218 nm, a network cementite grade of 0.5, and a martensite grade of 0.

[0152] (6) Mechanical peeling process The wire rod is passed through three sets of bending rollers and three sets of reverse bending rollers in sequence, and then the surface of the wire rod is brushed by a pair of rotating wire brushes.

[0153] After mechanical descaling, the oxide scale removal rate on the surface of the wire rod is 98.5%.

[0154] (7) Rough drawing process High-carbon steel wire rod is drawn into steel wire with a diameter of 3.0 mm using dry drawing. The drawing process consists of 7 passes, with a deformation of ≤19% per pass and a drawing speed of 7.2 m / s.

[0155] (8) Intermediate drawing process Dry drawing is used to draw the rough-drawn steel wire into a steel wire with a diameter of 1.6 mm. The drawing process consists of 8 passes, with a deformation of ≤17% per pass and a drawing speed of 12.3 m / s.

[0156] (9) Heat treatment process The steel wire obtained from the intermediate drawing process is heated and kept at a constant temperature, and then subjected to a lead bath.

[0157] The heating temperature is 930℃, the holding time is 50s, the lead bath temperature is 560℃, and the lead bath time is 86s.

[0158] (10) Brass plating process The steel wire that has undergone the heat treatment process is then subjected to copper plating, zinc plating, and thermal diffusion to obtain a steel wire with a brass plating layer.

[0159] The copper plating electrolyte is an acidic sulfate copper plating electrolyte with a copper sulfate concentration of 210 g / L and a current density of 3.5 A / dm³. 2 The zinc plating electrolyte used is an alkaline zincate zinc plating electrolyte with a zinc oxide concentration of 13 g / L and a current density of 12.2 A / dm³. 2 The temperature for controlled thermal diffusion was 548℃, and the thermal diffusion time was 20s.

[0160] The brass coating of the obtained brass-plated steel wire contains 64% copper by mass.

[0161] (11) Wet drawing process In a water tank wire drawing machine, steel wire is drawn at high speed with lubricant to obtain a steel wire with a diameter of 0.225mm.

[0162] The drawing process involves 26 passes, with a single pass deformation of ≤15%, a drawing speed of 11.9 m / s, and a working cone angle of 15°.

[0163] (12) Twisting process Steel cord is produced by twisting multiple strands of steel wire after the wet drawing process. The tension of the steel wire during twisting is controlled to be 9% of the breaking tensile force, the twist pitch is 13 times the diameter of the steel wire, the twisting speed is 3000 rpm, and the overtwist compensation coefficient is 1.023.

[0164] The wire breakage rate of steel cord during the production process is ≤1.5 times / ton.

[0165] Comparative Example The following section describes the various processes involved in the production of high-carbon steel wire rod and steel cord.

[0166] (1) Electric furnace smelting process The electric furnace smelting process is carried out in an electric furnace.

[0167] The raw materials for electric arc furnace smelting include scrap steel and molten iron, with scrap steel accounting for 80% of the raw materials by mass.

[0168] (2) LF refining process The molten steel obtained from the electric arc furnace smelting process is sent to the LF furnace for refining in order to adjust the chemical composition and inclusions.

[0169] Specifically, when molten steel arrives at the LF furnace, its temperature is measured and sampled. Then, it is heated by electricity to adjust the temperature of the molten steel. Then, based on the chemical composition measured by the sample taken at the furnace, alloys and carbon powder are added to carry out alloying. After that, slag-forming materials are added to the molten steel to form slag.

[0170] The chemical composition of the molten steel obtained from the LF refining process, by mass percentage, includes: C 0.80%, Si 0.20%, Mn 0.50%, S 0.012%, P 0.015%, Al 0.003%, O 0.002%, N 0.004%, Cu 0.30%, Ni 0.25%, Cr 0.12%, Mo 0.012%, Sn 0.012%, Sb 0.012%, As 0.012%, with the remainder being Fe and unavoidable impurities.

[0171] Among them, the residual element factor σ = 1.054%.

[0172] (3) Continuous casting process The molten steel obtained from the LF refining process is sent to a continuous caster for continuous casting to obtain a square billet with a cross-sectional dimension of 150 mm × 150 mm.

[0173] The continuous caster used is the same as that in Example 1.

[0174] The superheat of the molten steel during casting is controlled to 30°C; the current for mold electromagnetic stirring is 300 A, and the frequency is 3.5 Hz; the continuous casting drawing speed is 2.6 m / min; the specific water flow in the secondary cooling zone is 1.6 L / kg; the current for final solidification electromagnetic stirring is 400 A, and the frequency is 4 Hz; the fixed soft reduction amount at the final solidification position is 4 mm; the entrance temperature of the straightening zone is controlled to 920°C.

[0175] (4) High-speed wire rolling process The continuous casting billet obtained from the continuous casting process is heated and then rolled to obtain a wire rod with a diameter of 5.5 mm. The heating is performed in a heating furnace, the heating furnace adopts an oxidizing atmosphere, the air-fuel ratio is 1.2, and the pressure in the furnace chamber is controlled to 40 Pa. The temperature of the soaking section during heating is 1120°C, the soaking time is 35 min, the starting rolling temperature is 1030°C, and the laying temperature is 900°C.

[0176] (5) Stelmor cooling process When the temperature T≥700°C, the cooling rate is controlled at 15°C / s; when 500°C<T<700°C, the cooling rate is controlled at 15°C / s; when T≤500°C, the cooling rate is controlled at 9°C / s.

[0177] The microstructure and properties of the wire rod are tested, including: In terms of mechanical properties, sampling is performed on the wire rod by a tensile testing machine and mechanical property tests are carried out with reference to the standard test method and definition specified in GB / T 2975-2018 "Steel and steel products - Location and preparation of samples for mechanical testing".

[0178] The measured tensile strength of the high carbon steel wire rod is 940 MPa, the strength difference within the same coil is 45 MPa, the reduction of area is 23%, and the wire breaking rate during drawing is 5 times per ton.

[0179] In terms of microstructure and properties, with reference to GB / T 13298-2025 "Method for inspection of metallographic microstructure of metals", it is measured that the microstructure of the wire rod is sorbite + pearlite + ferrite + martensite, the sorbite ratio is only 72%, the lamellar spacing of sorbite is 260 nm, the grade of network cementite is 2.5, and the grade of martensite is 2.0.

[0180] (6) Mechanical descaling process The wire rod is sequentially passed through 2 groups of bending rollers and 2 groups of reverse bending rollers, after which the surface of the wire rod is brushed and ground by a pair of rotating wire brushes.

[0181] After mechanical descaling, the oxide scale removal rate on the surface of the wire rod is 85%.

[0182] (7) Rough drawing process High-carbon steel wire rods are drawn into steel wires with a diameter of 2.8 mm using a dry drawing process. The drawing process consists of 4 passes, with a deformation of ≤23% per pass and a drawing speed of 8.5 m / s.

[0183] (8) Intermediate drawing process Dry drawing is used to draw the rough-drawn steel wire into a steel wire with a diameter of 1.2 mm. The drawing process consists of 6 passes, with a deformation of ≤23% per pass and a drawing speed of 14 m / s.

[0184] (9) Heat treatment process The steel wire obtained from the intermediate drawing process is heated and kept at a constant temperature, and then subjected to a lead bath.

[0185] The heating temperature is 900℃, the holding time is 40s, the lead bath temperature is 580℃, and the lead bath time is 60s.

[0186] (10) Brass plating process The steel wire that has undergone the heat treatment process is then subjected to copper plating, zinc plating, and thermal diffusion to obtain a steel wire with a brass plating layer.

[0187] The copper plating electrolyte is an acidic sulfate copper plating electrolyte with a copper sulfate concentration of 170 g / L and a current density of 2.0 A / dm³. 2 The zinc plating electrolyte used is an alkaline zincate zinc plating electrolyte with a zinc oxide concentration of 8 g / L and a current density of 1.3 A / dm³. 2 The temperature for controlled thermal diffusion was 535℃, and the thermal diffusion time was 8s.

[0188] The brass coating of the obtained brass-plated steel wire has a copper mass percentage of 58%.

[0189] (11) Wet drawing process In a water tank wire drawing machine, steel wire is drawn at high speed with lubricant to obtain a steel wire with a diameter of 0.225mm.

[0190] The drawing process involves 20 passes, with a deformation of ≤14% per pass, a drawing speed of 15m / s, and a working cone angle of 17°.

[0191] (12) Twisting process Steel cord is produced by twisting multiple strands of steel wire after the wet drawing process. The tension of the steel wire during twisting is controlled to be 13% of the breaking tensile force, the twist pitch is 16 times the diameter of the steel wire, the twisting speed is 3800 rpm, and the overtwist compensation coefficient is 1.08.

[0192] The breakage rate of steel cord during the production process reaches 8 times per ton.

[0193] It should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This way of describing the specification is only for clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

[0194] The detailed descriptions listed above are merely specific descriptions of feasible implementation methods of this application, and are not intended to limit the scope of protection of this application. All equivalent implementation methods or modifications made without departing from the spirit of the art of this application should be included within the scope of protection of this application.

Claims

1. A method for producing steel cord, characterized in that, The steel cord is made from high-carbon steel wire rod through a series of processes including mechanical peeling, rough drawing, intermediate drawing, heat treatment, brass plating, wet drawing, and strand twisting. The chemical composition of the high-carbon steel wire rod, by mass percentage, includes: C 0.68~0.86%, Si 0.10~0.30%, Mn 0.30~0.60%, S≤0.015%, P≤0.020%, Al≤0.005%, O≤0.003%, N≤0.005%, Cu≤0.35%, Ni≤0.30%, Cr≤0.30%, Mo≤0.015%, Sn≤0.015%, Sb≤0.015%, As≤0.015%, with the remainder being Fe and unavoidable impurities; wherein, the residual element factor σ≤1.1%, σ=Cu+Ni+3(Cr+Mo+Sn)+15N+0.5(Sb+As); In the heat treatment process, the steel wire obtained from the intermediate drawing process is heated and held at a certain temperature, followed by a lead bath. Specifically, when σ ≤ 0.3%, the heating temperature is (895 + 3000σ)℃ ~ (905 + 3000σ)℃, the holding time is (32 + 2000σ)s ~ (38 + 2000σ)s, the lead bath temperature is (525 + 3000σ)℃ ~ (535 + 3000σ)℃, and the lead bath time is (62 + 2000σ)s ~ (68 + 2000σ)s; when 0.3% < σ ≤ 0.7%, the heating temperature is (905 + 1500σ)℃ ~ (915 + 1500σ)℃, and the holding time is (… 38+1000σ)s~(43+1000σ)s, lead bath temperature is (535+1500σ)℃~(545+1500σ)℃, lead bath time is (68+1500σ)s~(73+1500σ)s; when 0.7%<σ≤1.1%, heating temperature is (915+1000σ)℃~(925+1000σ)℃, holding time is (43+500σ)s~(48+500σ)s, lead bath temperature is (545+1000σ)℃~(555+1000σ)℃, lead bath time is (73+1000σ)s~(78+1000σ)s; In the brass plating process, the steel wire that has undergone the heat treatment process is sequentially copper-plated, zinc-plated, and thermally diffused to obtain a steel wire with a brass coating. The thermal diffusion time is 10~25s. Specifically, when σ≤0.3%, the temperature during thermal diffusion is 540~550℃; when 0.3%<σ≤0.7%, the temperature during thermal diffusion is 550~560℃; and when 0.7%<σ≤1.1%, the temperature during thermal diffusion is 560~570℃.

2. The method for producing steel cord according to claim 1, characterized in that, In the rough drawing process, when σ≤0.3%, the number of drawing passes is 6~7, the deformation of a single drawing pass is ≤21%, and the drawing speed is 7.0~8.0m / s; When 0.3% < σ ≤ 0.7%, the number of drawing passes is 8 to 9, the deformation per single drawing pass is ≤ 19%, and the drawing speed is 5.5 to 6.5 m / s; When 0.7% < σ ≤ 1.1%, the number of drawing passes is 10 to 11, the deformation per single drawing pass is ≤ 17%, and the wire drawing speed is 4.5 to 5.0 m / s.

3. The method for producing steel cord according to claim 1, characterized in that, In the intermediate drawing process, when σ≤0.3%, the number of drawing passes is 7~8, the deformation of a single drawing pass is ≤20%, and the drawing speed is 12.0~13.0m / s; When 0.3% < σ ≤ 0.7%, the number of drawing passes is 9 to 10, the deformation per single drawing pass is ≤ 18%, and the wire drawing speed is 10.5 to 11.5 m / s; When 0.7% < σ ≤ 1.1%, the number of drawing passes is 11 to 12, the deformation per single drawing pass is ≤ 16%, and the wire drawing speed is 10.0 to 11.0 m / s.

4. The method for producing steel cord according to claim 1, characterized in that, In the wet drawing process, when σ≤0.3%, the number of drawing passes is 24~26, the deformation of a single drawing pass is ≤16%, the drawing speed is (17.5-700σ)m / s~(18.5-700σ)m / s, and the angle of the working cone is 14~16°; When 0.3% < σ ≤ 0.7%, the number of drawing passes is 26 to 28, the deformation per drawing pass is ≤ 15%, the drawing speed is (15.5-300σ) m / s to (16.5-300σ) m / s, and the angle of the working cone is 11 to 13°. When 0.7% < σ ≤ 1.1%, the number of drawing passes is 28 to 30, the deformation per pass is ≤ 14%, the drawing speed is (13.5-200σ) m / s to (14.5-200σ) m / s, and the angle of the working cone is 8 to 10°.

5. The method for producing steel cord according to claim 1, characterized in that, In the twisting process, the steel wire after the wet drawing process is twisted into multiple strands. When σ≤0.3%, the tension of the steel wire during twisting is controlled to be 8~12% of the breaking tensile force, the twist pitch is 12~15 times the diameter of the steel wire, the twisting speed is 2300~3500rpm, and the overtwist compensation coefficient is 1.01~1.03; When 0.3% < σ ≤ 0.7%, the tension of the steel wire during twisting should be 6 to 10% of the breaking tensile force, the twist pitch should be 15 to 18 times the diameter of the steel wire, the twisting speed should be 2000 to 3000 rpm, and the overtwist compensation coefficient should be 1.04 to 1.

07. When 0.7% < σ ≤ 1.1%, the tension of the steel wire during twisting should be controlled to be 5~8% of the breaking tensile force, the twist pitch should be 18~20 times the diameter of the steel wire, the twisting speed should be 1500~2500 rpm, and the overtwist compensation coefficient should be 1.08~1.

10.

6. The method for producing steel cord according to claim 1, characterized in that, In the brass plating process, the copper plating electrolyte is an acidic sulfate copper plating electrolyte with a copper sulfate concentration of 180~220 g / L and a current density of 2.5~4.0 A / dm³. 2 The zinc plating electrolyte is an alkaline zincate zinc plating electrolyte with a zinc oxide concentration of 10~15 g / L and a current density of 1.5~2.5 A / dm³. 2 .

7. The method for producing steel cord according to claim 1, characterized in that, The brass plating layer of the steel wire obtained by the brass plating process has a copper mass percentage of 61-66%.

8. The method for producing steel cord according to claim 1, characterized in that, The diameter of the steel wire obtained in the rough drawing process is 2.8~3.2mm, the diameter of the steel wire obtained in the intermediate drawing process is 1.4~1.8mm, and the diameter of the steel wire obtained in the wet drawing process is 0.175~0.35mm.

9. The method for producing steel cord according to claim 1, characterized in that, In the mechanical peeling process, the wire rod is passed through a bending roller group and a reverse bending roller group in sequence, and then a rotating wire brush is used to brush the surface of the wire rod to remove the oxide scale on the surface of the wire rod.

10. A steel cord, characterized in that, The steel cord is prepared using the steel cord production method as described in any one of claims 1 to 9.